Pandemic, Economic Crisis and public revenue: the impacts of Complementary Law 173/2020 on personnel costs in the municipalities of the northeastern region of Santa Catarina - Heinig, Daniel Wagner; Myszczuk, Ana Paula (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2021)
In addition to being a sanitary crisis, the COVID-19 pandemic has also led to an economic crisis in Brazilian society. An obvious consequence of this economic crisis resulting from the pandemic is the fall in public revenue. The reduced consumption of goods and services by families in times of crisis has a negative fiscal impact, which in turn affects government expenditure and investments, leading to even less economic activity. In an attempt to mitigate the effects of the crisis, the Federal Program to Confront the SARS-CoV-2 Coronavirus (Covid-19) was created through Complementary Law 173/2020 to bring relief to municipalities and other subnational entities, but under the imposition of a number of controls on personnel costs. The present study sought to analyze the impact of the economic crisis caused by the pandemic on municipal tax revenues in the northeastern region of Santa Catarina State. The study also evaluated the extent to which Complementary Law 173/2020 helped to sustain the personnel costs of the executive branch of these municipalities. The results of the study showed that there was an average reduction of 4.21% in municipal Current Net Revenues, especially in Joinville, with a reduction of 6.86%, and Campo Alegre (10.51%). The study also showed that Complementary Law 173/2020 helped to sustain personnel costs in the executive branch of the municipalities in question. Personnel costs remained within the maximum and prudential limits set by the Fiscal Responsibility Law. Nevertheless, five municipalities registered an increase in terms of percentages, notably related to the fall in Current Net Revenues during the period under study.